Pengaruh E-Commerce Tokopedia dan Kerja Sama Aplikasi Tiktok pada E-Commerce Tokopedia Terhadap Minat Beli Konsumen - Dina Amalia Khoirun Nadha Raswadiyanto; Deny Ardiansyah; Edita Rachma Kamila (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of Tokopedia's e-commerce strategy and collaboration with the TikTok application on consumer purchasing interest. Using quantitative methods, data were collected through a survey with a questionnaire distributed to 90 respondents who are active users of Tokopedia and TikTok. The analysis technique used is multiple regression to test the relationship between the independent variables (Tokopedia's e-commerce strategy and collaboration with TikTok) and the dependent variable (consumer purchasing interest). The results of the study indicate that Tokopedia's e-commerce strategy has a positive and significant influence on consumer purchasing interest, as well as the collaboration between Tokopedia and TikTok which has proven to be significant in increasing purchasing interest. In addition, the simultaneous influence between the two variables shows stronger results than the individual influence. This study provides a practical contribution to the e-commerce industry in formulating more effective marketing strategies in the digital era.